2017
DOI: 10.4013/nbc.2017.121.05
|View full text |Cite
|
Sign up to set email alerts
|

Density of invasive exotic palms affecting the understory avifauna in the Atlantic forest, Southeastern Brazil

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution 4.0 International (CC BY 4.0), which permits reproduction, adaptation, and distribution provided the original author and source are credited. ResumoA invasão biológica é um processo frequente em ambientes naturais do mundo inteiro. Em locais invadidos, é necessária a avaliação da interferência da espécie invasora no ecossistema, antes que medidas de manejo sejam adotadas. Trechos do Parque Estadual Alberto Löfgren (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Besides, forest fragments where E. edulis is now extinct or has small populations because of intensive harvesting, may still harbor a frugivore assemblage that is capable of dispersing A. cunninghamiana seeds and facilitating its establishment (Mengardo and Pivello 2014). Moreover, high densities of the invasive plant in fragments can act synergistically with the frugivores by increasing the presence and abundance of generalist birds (Campagnoli and Antunes 2017). We found that A. cunninghamiana interacts with a higher proportion of generalist than E. edulis.…”
Section: Discussionmentioning
confidence: 73%
“…Besides, forest fragments where E. edulis is now extinct or has small populations because of intensive harvesting, may still harbor a frugivore assemblage that is capable of dispersing A. cunninghamiana seeds and facilitating its establishment (Mengardo and Pivello 2014). Moreover, high densities of the invasive plant in fragments can act synergistically with the frugivores by increasing the presence and abundance of generalist birds (Campagnoli and Antunes 2017). We found that A. cunninghamiana interacts with a higher proportion of generalist than E. edulis.…”
Section: Discussionmentioning
confidence: 73%
“…Embora a proporção de espécies polinizadas ou dispersas por animais seja semelhante à encontrada em florestas maduras, um indicador negativo e preocupante é o fato das exóticas ocuparem mais de 10% da riqueza e mais de 20% dos indíviduos desses grupos funcionais: o processo de invasão biológica pode aumentar, com o agravante de comprometer a sucessão natural, considerando que essas exóticas invasoras já estabeleceram relações com a fauna polinizadora e dispersora local [58,59,60].…”
Section: Discussionunclassified